Enhancing graduate employability through interdisciplinary, work‐based learning - Aisha Abuelmaatti; Leon Vinokur (Journal of Learning Development in Higher Education)
This paper examines an interdisciplinary initiative at Queen Mary University of London (QMUL), focusing on the collaboration between qTech and qNomics in delivering a multi-disciplinary project designed to bridge the gap between academic learning and professional experience. The collaboration fosters direct engagement with industry and provides students with authentic, real-world learning opportunities that are crucial for enhancing their employability. This initiative goes beyond traditional academic frameworks, offering students not only an opportunity to engage in practical problem solving but also a platform for reflecting on their work. In doing so, it contributes significantly to knowledge exchange while simultaneously providing a foundation for professional competencies and reflective practice. By exploring the structure and outcomes of this collaboration, the paper highlights how such interdisciplinary projects can strengthen graduate attributes, enhance work-based education, and better prepare students for the challenges of the contemporary workforce.